Indian consumers animosity level on Chinese products and services– impact of post galwan stand off - PARAMASIVAN, SENTHILMURUGAN; SANKAR, MALLIKA; CHELLASAMY, AARTHY; N, AISHWARYA (The journal of contemporary issues in business and government, 2021)
The intention of this paper is to ascertain the preferences of Indian consumers towardsproduct and services originated from China specifically aftermath ofGalwan valley border clash between Indian and Chinese soldiers in Ladakh region where 20 Indian soldiers martyred in June, 2020. This incident escalated the tension in India as a sentiment among patriotic Indian consumer group who called for boycotting Chinese products and service. The episode of anti- Chinese consumption demonstrated by some political outfits in India by burning and breaking Chinese products in the streets to catch the attentions of international media and pertinent business groups.The Chinese products and services are preferred by the wide range of Indian consumer segments since they perceive decent value for their money. This paper attemptedto discoverthe effect of Galwan tussle and subsequent political developments between two nations on significant impact in the perceptions and preferences of Indian consumers over Chinese products and services. The current user status fortenhighly demandedChinese products and services categories were identified and enquiredwhether the consumers have intention to maintain their status-quo in preferring product and services originated from China in the future as well. This research also surveyed about reason for changing preference of products and services from China.